Non-invasive mapping reduces procedure duration for catheter ablation of premature ventricular contractions using 12 lead ECG information: results from a prospective case-control study. (14th October 2021) - Griffiths, J; Cazzoli, I; Ailoaei, S; Guarguaglia, S; Kempny, A; Ernst, S
Abstract: Background: Premature ventricular complexes (PVCs) result from early depolarisation of myocardial tissue in the ventricles and can ultimately lead to PVC-induced cardiomyopathy. Catheter ablation aims to completely eliminate the PVCs and is usually carried out using sequential activation mapping techniques. We report the results of a prospective case-control trial using the non-invasive, simultaneous 3D mapping system View into Ventricular Onset (VIVO) in combination with a 12 lead Holter ECG recording for catheter ablation of PVC. Methods and results: A total of 16 patients (mean age 52.1±20.8 years, all structurally normal hearts, were enrolled and underwent VIVO mapping as a preparation of their invasive PVC ablation. Pre-ablation PVC burden had a median of 18.7% (IQR; 9.94 – 24.35). All but one patient (with very low PVC burden and epicardial origin) underwent a catheter ablation attempt guided by the 3D non-invasive maps integrated as VTK files in to the EAM. In 13/15 patients, acute elimination of the PVC was achieved which resulted in a PVC burden of <0.1% at 3 months' time. Procedure time amounted to in median 106 minutes (IQR 92.5 – 135.5), whereas in an age- and gender-matched control cohort (2:1) procedure time was significantly longer (145 (123.0 – 190.5). Conclusion: Ward-based non-invasive 3D mapping (VIVO) of the origin of PVCs in patients with structurally normal hearts successfully guided the invasive ablation procedure and significantly reduced the invasive procedure time, as compared to a contemporary age- and gender-matched control cohort. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Catheter Precision